2013
DOI: 10.5194/hess-17-3795-2013
|View full text |Cite
|
Sign up to set email alerts
|

Is high-resolution inverse characterization of heterogeneous river bed hydraulic conductivities needed and possible?

Abstract: Abstract. River-aquifer exchange fluxes influence local and regional water balances and affect groundwater and river water quality and quantity. Unfortunately, river-aquifer exchange fluxes tend to be strongly spatially variable, and it is an open research question to which degree river bed heterogeneity has to be represented in a model in order to achieve reliable estimates of river-aquifer exchange fluxes. This research question is addressed in this paper with the help of synthetic simulation experiments, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
(46 reference statements)
2
20
0
Order By: Relevance
“…This is especially true of discharge. Similar effects have been observed in other studies (Kalbus et al, 2009;Kurtz et al, 2013;Mendoza et al, 2015;Lackey et al, 2015).…”
Section: Summary and Concluding Remarkssupporting
confidence: 78%
See 1 more Smart Citation
“…This is especially true of discharge. Similar effects have been observed in other studies (Kalbus et al, 2009;Kurtz et al, 2013;Mendoza et al, 2015;Lackey et al, 2015).…”
Section: Summary and Concluding Remarkssupporting
confidence: 78%
“…Schmidt et al (2006) also studied the spatial distribution and magnitude of groundwater discharge to a stream with a simple analytical model that was mainly focused on groundwater discharge at the reach scale. Kurtz et al (2013) generated multiple realizations of stream-aquifer interactions in the Limmat aquifer system in Zurich Switzerland. They allowed riverbed hydraulic conductivities to take one of four different levels of heterogeneity ranging from local variability at each grid point to effective conductances of only 5, 3, and 2 values.…”
Section: Introductionmentioning
confidence: 99%
“…Data assimilation (DA) is one possible inverse modeling method for this purpose (Chen & Zhang, ; Hendricks Franssen & Kinzelbach, ). Until now DA has already been successfully applied for estimating K rb in several cases (e.g., Alzraiee et al, ; Hendricks Franssen et al, ; Kurtz et al, ; Kurtz et al, ; Kurtz et al, ; Tang et al, ; Tang et al, ). Hendricks Franssen et al () estimated leakage coefficients for a limited number of zones together with aquifer hydraulic conductivity ( K aq ), using a 3‐D variably saturated GW flow model of the Limmat valley, Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…For other combinations of degree of connection at the calibration state and direction of movement of the water table, the estimated water fluxes could be both overpredicted or underpredicted, by as much as 35%, depending on the streambed heterogeneity. Kurtz et al [36] performed a similar investigation on a larger scale, using a model of the Limmat valley aquifer in Zurich, Switzerland. They compared water fluxes from the fully heterogeneous riverbed to water fluxes from an equivalent homogeneous riverbed and from rivers with two, three, or five leakage zones and found that the degree of accuracy of predicted water fluxes decreased as the simulated level of heterogeneity decreased.…”
Section: Introductionmentioning
confidence: 99%